A novel scale‐down mimic of perfusion cell culture using sedimentation in an automated microbioreactor (SAM). (23rd May 2019) - Kreye, Steffen; Stahn, Rainer; Nawrath, Karina; Goralczyk, Vicky; Zoro, Barney; Goletz, Steffen
Abstract: Continuous upstream processing in mammalian cell culture for recombinant protein production holds promise to increase product yield and quality. To facilitate the design and optimization of large‐scale perfusion cultures, suitable scale‐down mimics are needed which allow high‐throughput experiments to be performed with minimal raw material requirements. Automated microbioreactors are available that mimic batch and fed‐batch processes effectively but these have not yet been adapted for perfusion cell culture. This article describes how an automated microbioreactor system (ambr15) can be used to scale‐down perfusion cell cultures using cell sedimentation as the method for cell retention. The approach accurately predicts the viable cell concentration, in the range of about 1 × 10 7  cells/mL for a human cell line, and cell viability of larger scale cultures using a hollow fiber based cell retention system. While it was found to underpredict cell line productivity, the method accurately predicts product quality attributes, including glycosylation profiles, from cultures performed in bioreactors with working volumes between 1 L and 1, 000 L. The spent media exchange method using the ambr15 was found to predict the influence of different media formulations on large‐scale perfusion cultures in contrast to batch and chemostat experiments performed in the microbioreactor system. The described experimental setup in the microbioreactor allowed an 80‐fold reduction in cell culture media requirements, half the daily operator time, which can translate into a cost reduction of approximately 2.5‐fold compared to a similar experimental setup at bench scale.